Anti-glare laminate and method for producing same
By using an anti-glare laminate structure composed of polycarbonate resin, high hardness resin and hard coating on the front panel of the liquid crystal display device and mobile phone terminal, the problem of preventing image mapping, suppressing text blur, and having high scratch resistance and shape stability in the prior art is solved, and efficient anti-glare performance and scratch resistance are achieved.
Patent Information
- Application Number
- CN202380061956.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-13
- Filing Date
- 2023-09-04
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to realize an anti-glare laminate on the front panel of a liquid crystal display device and a mobile phone terminal, which both prevents image mapping, suppresses blurred text, and has high scratch resistance and shape stability.
An anti-glare laminate structure consisting of polycarbonate resin, high hardness resin and hard coating is adopted, where the interface extended area ratio, arithmetic average height and autocorrelation length of the hard coating meet a specific range to ensure the anti-glare performance and scratch resistance of the laminate.
It realizes the effect of preventing image mapping, suppressing text blur, and having high scratch resistance and shape stability on the front panel of equipment such as liquid crystal display devices and mobile phone terminals.
Smart Images

Figure BDA0005285222570000031 
Figure BDA0005285222570000051 
Figure BDA0005285222570000061
Abstract
Description
Technical Field
[0001] The present invention relates to an anti-glare laminate and a method for producing the same. More specifically, the present invention relates to an anti-glare laminate having both anti-glare performance and high scratch resistance and excellent shape stability, and used as a front panel of a vehicle-mounted liquid crystal display device or a mobile phone terminal, a personal computer, or a tablet PC, and a method for producing the same. Background Art
[0002] A liquid crystal display device is provided with a front plate for the purpose of protecting the liquid crystal panel, etc. As a conventional material for the front plate of a liquid crystal display device, (meth)acrylic resin represented by polymethyl methacrylate (PMMA) can be cited.
[0003] Furthermore, in recent years, sheets made of polycarbonate resin have been used as front panels due to their advantages of high impact resistance, heat resistance, secondary processability, light weight, and transparency. In particular, front panels in which a hard coating is applied to a multilayer sheet of a polycarbonate resin sheet laminated on the surface of the sheet have not only surface hardness and scratch resistance comparable to conventional acrylic resins with a hard coating, but also have the excellent impact resistance, heat resistance, processability, and transparency of polycarbonate resin, and are therefore widely used as front panels.
[0004] The front panel of a liquid crystal display device including the polycarbonate resin sheet is generally formed by a melt extrusion method together with an acrylic resin.
[0005] In a liquid crystal display device, an optical laminate for anti-reflection is usually provided on the outermost surface. This anti-reflection optical laminate is a product that uses light scattering or interference to suppress image reflection and reduce reflectivity.
[0006] As one of the optical laminates for anti-reflection, an anti-glare film having an anti-glare layer with a concavo-convex shape formed on the surface of a transparent substrate is known. This anti-glare film can scatter external light by utilizing the concavo-convex shape of the surface, thereby preventing the reduction of visibility due to reflection of external light and image reflection. In addition, since the optical laminate is usually provided on the outermost surface of a liquid crystal display device, it is also necessary to impart hard coating properties to prevent scratches during operation.
[0007] On the display surface of liquid crystal display devices and organic electroluminescent (EL) display devices, a mixture of microparticles and a binder resin or a curable resin is usually coated on the substrate to form fine concave and convex shapes on the surface to prevent specular reflection and image reflection. However, when the concave and convex shapes are provided to prevent image reflection, the scattering of the transmitted light propagating in a straight line increases, the pixel outline becomes unclear, and the text is blurred.
[0008] Furthermore, when fine particles are added to present surface irregularities, the fine particles on the outermost surface fall off during the scratch resistance test and act as abrasives, so that the scratch resistance is significantly reduced compared to the case where no fine particles are added, which is not preferred.
[0009] As described above, the front panels of vehicle-mounted liquid crystal display devices, mobile phone terminals, personal computers, and tablet computers do not yet have excellent impact resistance, heat resistance, image reflection prevention, and text blur suppression, and have anti-glare properties, high scratch resistance, and excellent shape stability. In Patent Document 1, microparticles are added to improve transmission clarity and reduce text blur. Although the addition of microparticles can increase pencil hardness, scratch resistance decreases, so it is not preferred.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Laid-Open No. 2010-160398 Summary of the invention
[0013] Problems to be solved by the invention
[0014] The present invention aims to solve at least one of the above-mentioned prior art problems. Furthermore, the present invention aims to provide an anti-glare laminate having both anti-reflection performance and text blur suppression performance, high scratch resistance and excellent shape stability, and a method for manufacturing the same.
[0015] Technical solutions to solve problems
[0016] The above-mentioned problems can be solved by the following present invention. That is, the present invention is as follows.
[0017] <1> An anti-glare laminate, comprising at least a substrate layer comprising a polycarbonate resin (a1), a high hardness resin layer comprising a high hardness resin (B), and a hard coating layer, wherein the interface expansion area ratio (Sdr), arithmetic mean height (Sa), and autocorrelation length (Sal) of the hard coating layer satisfy the following formulas (i) to (iii):
[0018] 0≤Sdr≤0.6 (i)
[0019] 0≤Sa≤0.16 (ii)
[0020] 0≤Sal≤15.0 (iii).
[0021] <2> According to the above <1> The anti-glare laminate, wherein the interface expansion area ratio (Sdr), arithmetic mean height (Sa) and autocorrelation length (Sal) of the hard coat layer satisfy the following formulas (iv) to (vi):
[0022] 0≤Sdr≤0.3 (iv)
[0023] 0.03≤Sa≤0.13 (v)
[0024] 3.0≤Sal≤8.0 (vi).
[0025] <3> According to the above <1> or <2> The anti-glare laminated body has a warpage change of less than 350 μm after being kept in an environment of a temperature of 85° C. and a relative humidity of 85% for 120 hours.
[0026] <4> According to the above <1> ~ <3> In any one of the above anti-glare laminates, the high-hardness resin layer has a thickness of 10 to 250 μm.
[0027] <5> According to the above <1> ~ <4> In any one of the above anti-glare laminates, a total thickness of the substrate layer and the high-hardness resin layer is 100 to 3000 μm.
[0028] <6> According to the above <1> ~ <5> In any one of the above anti-glare laminates, the hard coat layer contains no organic particles or inorganic particles.
[0029] <7> According to the above <1> ~ <6> The anti-glare laminate according to any one of the preceding claims, wherein the polycarbonate resin (a1) contains a component derived from a monohydric phenol represented by the following general formula (5).
[0030]
[0031] (Where R 5 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms, R 6 Each independently represents a hydrogen atom, a halogen, or an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms which may have a substituent, and n is an integer of 0 to 4, wherein the substituent is a halogen, an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms.)
[0032] <8> A vehicle-mounted display device comprising the above <1> ~ <7> The anti-glare laminate according to any one of the above.
[0033] <9> A touch panel front protection plate, comprising the above <1> ~ <7> The anti-glare laminate according to any one of the above.
[0034] <10> A front panel for OA (office automation) equipment, portable electronic equipment or television, comprising the above <1> ~ <7> The anti-glare laminate according to any one of the above.
[0035] <11> A method for producing an anti-glare laminate, which is used to produce the above <1> ~ <7> The anti-glare laminate according to any one of the preceding claims comprises the steps of pressing a patterned PET film onto the surface of a hard coat layer and transferring a concavo-convex shape so that the hard coat layer after the transfer satisfies the following formulas (i) to (iii),
[0036] 0≤Sdr≤0.6 (i)
[0037] 0≤Sa≤0.16 (ii)
[0038] 0≤Sal≤15.0 (iii).
[0039] Effects of the Invention
[0040] According to the present invention, an anti-glare laminate having both anti-reflection performance and anti-blurring performance, high scratch resistance and excellent shape stability, and a method for producing the same can be provided. DETAILED DESCRIPTION
[0041] The present invention will be described in detail below with reference to production examples and embodiments, but the present invention is not limited to the production examples or embodiments, and can be modified in any manner as long as it does not obviously exceed the scope of the present invention.
[0042] The anti-glare laminate of the present invention includes at least a substrate layer containing a polycarbonate resin (a1), a high-hardness resin layer containing a high-hardness resin, and a hard coat layer, which are arranged in this order.
[0043] The lamination sequence of the anti-glare laminate is preferably substrate layer-high hardness resin layer-hard coating layer. The other side surface of the substrate layer is not particularly specified. In one embodiment, a high hardness resin layer can be provided on the other side surface of the substrate layer. In this case, the anti-glare laminate has a structure of high hardness resin layer-substrate layer-high hardness resin layer-hard coating layer. In addition, in one embodiment, a high hardness resin layer and a hard coating layer can also be provided on the other side surface of the substrate layer. In this case, the anti-glare laminate has a structure of hard coating layer-high hardness resin layer-substrate layer-high hardness resin layer-hard coating layer.
[0044] In the case where the high hardness resin layer is provided on both sides of the substrate layer, for the sake of shape stability, it is more preferred that the same high hardness resin layer is used on both sides of the surface. In addition, in the case where the hard coating is provided on both sides of the substrate, it is more preferred that the same hard coating is provided on both sides of the surface from the viewpoint of improving shape stability. In addition, the substrate layer and the high hardness resin layer and the high hardness resin layer and the hard coating can be directly laminated respectively, or can be laminated across other layers, but it is preferred to be directly laminated.
[0045] In one embodiment, the anti-glare laminate can be used as an in-vehicle display device for, for example, a car navigation system, a central information display (CID), a rear seat entertainment system (RSE), an instrument panel assembly, a touch panel full-screen protection plate, and a front panel for OA equipment, a portable electronic device, a television, etc. In addition, the front panel can be used alone as a front panel of a liquid crystal display device, or can be used as a front panel by laminating with other substrates such as a touch sensor.
[0046] The various components of the anti-glare laminate of the present invention will be described below.
[0047] <Base material layer>
[0048] The substrate layer contains a polycarbonate resin (a1). The substrate layer may further contain additives and the like.
[0049] [Polycarbonate resin (a1)]
[0050] The polycarbonate resin (a1) is not particularly limited as long as it is a compound containing a carbonate bond, i.e., -[O-R-OCO]- unit (R may contain an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and may have a linear structure or a branched structure) in the main chain of the molecule. It is particularly preferred to use a polycarbonate resin containing a structural unit of the following formula (4). By using such a polycarbonate resin, a resin laminate having excellent impact resistance can be obtained.
[0051]
[0052] Specifically, as the polycarbonate resin (a1), an aromatic polycarbonate resin (for example, trade names of IUPILON S-2000, IUPILON S-1000, and IUPILON E-2000 manufactured by Mitsubishi Engineering-Plastics Corporation) etc. can be used, but the present invention is not limited to these.
[0053] In recent years, there has been an increasing demand for bending of front panels, and therefore, as the polycarbonate resin (a1), it is preferred to use a monohydric phenol represented by the following general formula (5) as a terminal terminator.
[0054]
[0055] In the formula, R 5 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms, R 6 Each independently represents a hydrogen atom, a halogen, an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms which may have a substituent, and n is an integer of 0 to 4, wherein the substituent is a halogen, an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms. In the present specification, "alkyl" and "alkenyl" may be straight-chain or branched, and may have a substituent.
[0056] More preferably, the monohydric phenol represented by the general formula (5) is represented by the following general formula (6).
[0057]
[0058] In the formula, R 5 It represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms.
[0059] In the general formula (5) or (6), R 5 The number of carbon atoms in R is more preferably within a specific numerical range. 5 The upper limit of the number of carbon atoms is preferably 36, more preferably 22, and particularly preferably 18. 5 The lower limit of the number of carbon atoms is preferably 8, and more preferably 12.
[0060] When R in the general formula (5) or the general formula (6) 5 When the upper limit of the number of carbon atoms is appropriate, the solubility of the monohydric phenol (terminator) in an organic solvent tends to increase, and the productivity in the production process of the polycarbonate resin is improved, which is preferred.
[0061] As an example, when R 5 When the number of carbon atoms is less than 36, the productivity is high and the economy is good in the manufacture of polycarbonate resin; when R 5 When the number of carbon atoms is 22 or less, the solubility of the monohydric phenol in an organic solvent is particularly excellent, and the productivity is extremely high and the economic efficiency is also improved when producing a polycarbonate resin.
[0062] When R in the general formula (5) or the general formula (6) 5 When the lower limit of the number of carbon atoms is appropriate, the glass transition temperature of the polycarbonate resin can be prevented from being too high, thereby achieving appropriate thermoformability, which is preferred.
[0063] For example, when R in the general formula (6) is used 5In the case of a monophenol (terminator) having an alkyl group with 16 carbon atoms, the monophenol has excellent glass transition temperature, melt fluidity, moldability, anti-dripping property, and solvent solubility during the production of the polycarbonate resin, and is particularly preferably used as a terminator for the polycarbonate resin of the present invention.
[0064] Among the monohydric phenols (terminator) represented by the general formula (5) or (6), it is particularly preferable to use either or both of hexadecyl p-hydroxybenzoate and 2-hexyldecyl p-hydroxybenzoate as the terminator.
[0065] The weight average molecular weight of the polycarbonate resin (a1) is preferably 15000 to 75000, more preferably 20000 to 70000, and further preferably 20000 to 65000. When the weight average molecular weight of the polycarbonate resin (a1) is 15000 or more, it is preferred because the impact resistance is increased. On the other hand, when the weight average molecular weight is 75000 or less, it is preferred because thermal stability can be maintained even when the molding conditions are high temperatures that can form the substrate layer with less heat source. Among them, in this specification, the weight average molecular weight is the weight average molecular weight converted to standard polystyrene measured by gel permeation chromatography (GPC).
[0066] The polycarbonate resin (a1) contained in the base material layer may be one kind or two or more kinds.
[0067] The content of the polycarbonate resin (a1) in the substrate layer is preferably 75% by mass or more, more preferably 90% by mass or more, and further preferably 100% by mass, based on the total mass of the substrate layer, from the viewpoint of improving impact resistance.
[0068] [additive]
[0069] The base material layer may further contain additives.
[0070] As additives, substances commonly used in anti-glare laminates can be used. As additives, for example, antioxidants, anti-coloring agents, antistatic agents, release agents, lubricants, dyes, pigments, plasticizers, flame retardants, resin modifiers, solubilizers, reinforcing materials such as organic fillers or inorganic fillers can be cited.
[0071] The amount of the additive is preferably 0 to 10% by mass, more preferably 0 to 7% by mass, and particularly preferably 0 to 5% by mass, based on the total mass of the base material layer.
[0072] The method for mixing the additives and the resin is not particularly limited, and a total amount blending method, a masterbatch dry blending method, a total amount dry blending method, etc. may be used.
[0073] [Constitution of base material layer]
[0074] The thickness of the substrate layer is preferably 0.3 to 10 mm, more preferably 0.3 to 5 mm, and particularly preferably 0.3 to 3.5 mm.
[0075] <High Hardness Resin Layer>
[0076] The high hardness resin layer contains a high hardness resin. In addition, the high hardness resin layer may further contain additives and the like as needed. By providing a high hardness resin layer between the substrate layer and the hard coating layer, an anti-glare laminate having high shape stability can be obtained. In addition, the high hardness resin layer can have functions such as improving the hardness of the anti-glare laminate. Among them, in this specification, the high hardness resin refers to a resin having a higher hardness than the polycarbonate resin used as a substrate, and refers to a resin having a pencil hardness of HB or above, preferably HB to 3H, more preferably H to 3H, and further preferably 2H to 3H. Among them, the pencil hardness of the high hardness resin layer is the evaluation result of the pencil scratch hardness test according to JIS K 5600-5-4:1999. Specifically, a pencil is pressed on the surface of the high hardness resin layer at an angle of 45 degrees and a load of 750g, and the hardness is gradually increased, and the hardness of the hardest pencil that does not cause a scratch is evaluated as the pencil hardness.
[0077] [High hardness resin]
[0078] The high hardness resin is not particularly limited, but preferably contains at least one selected from resins (B1) to (B6). Even when resins (B1) to (B6) are resin compositions containing a plurality of resins, they may also be referred to as resins (B1) to (B6).
[0079] (Resin (B1))
[0080] Resin (B1) is a copolymer resin comprising a (meth)acrylate structural unit (a) represented by the following general formula (1) and an aliphatic vinyl structural unit (b) represented by the following general formula (2). In this case, the resin (B1) (copolymer resin) may also have other structural units. The total proportion of the (meth)acrylate structural unit (a) and the aliphatic vinyl structural unit (b) is 90 to 100 mol%, preferably 95 to 100 mol%, and more preferably 98 to 100 mol% of all structural units of the copolymer resin. In addition, the proportion of the (meth)acrylate structural unit (a) is 65 to 80 mol% of all structural units of the copolymer resin.
[0081] In this specification, (meth)acrylic acid means methacrylic acid and / or acrylic acid.
[0082]
[0083] In the formula, R 1It is a hydrogen atom or a methyl group, and is preferably a methyl group.
[0084] In addition, R 2 is an alkyl group having 1 to 18 carbon atoms, preferably an alkyl group having 1 to 10 carbon atoms, and more preferably an alkyl group having 1 to 6 carbon atoms. Specific examples thereof include methyl, ethyl, butyl, lauryl, stearyl, cyclohexyl, and isobornyl. 2 Preferred is a methyl group or an ethyl group, and more preferred is a methyl group.
[0085] Among them, in R 2 When R is a methyl group or an ethyl group, the (meth)acrylate structural unit (a) represented by the general formula (1) becomes a (meth)acrylate structural unit. 1 is methyl and R 2 In the case of a methyl group, the (meth)acrylate structural unit (a) represented by the general formula (1) becomes a methyl methacrylate structural unit.
[0086] The (meth)acrylate structural unit (a) represented by the general formula (1) in the resin (B1) may contain only one kind or two or more kinds.
[0087]
[0088] In the formula, R 3 It is a hydrogen atom or a methyl group, and is preferably a hydrogen atom.
[0089] R 4 It is a cyclohexyl group which may be substituted by a hydrocarbon group having 1 to 4 carbon atoms, and preferably a cyclohexyl group without a substituent. In the present specification, the "hydrocarbon group" may be linear, branched, or cyclic, and may have a substituent.
[0090] In R 3 is a hydrogen atom and R 4 In the case of a cyclohexyl group, the aliphatic vinyl structural unit (b) represented by the general formula (2) becomes a vinylcyclohexane structural unit.
[0091] The aliphatic vinyl structural unit (b) represented by the general formula (2) in the resin (B1) may contain only one kind or two or more kinds.
[0092] The other structural units are not particularly limited, and examples thereof include structural units derived from aromatic vinyl monomers containing unhydrogenated aromatic double bonds produced in the process of manufacturing resin (B1) by polymerizing (meth)acrylate monomers and aromatic vinyl monomers and then hydrogenating aromatic double bonds derived from the aromatic vinyl monomers, etc. Specific examples of the other structural units include styrene structural units.
[0093] The resin (B1) may contain only one type of other structural unit, or may contain two or more types.
[0094] The content of the (meth)acrylate structural unit (a) represented by the general formula (1) is 65 to 80 mol%, preferably 70 to 80 mol%, relative to the total structural units of the above-mentioned resin (B1) (copolymer resin). When the content of the (meth)acrylate structural unit (a) is 65 mol% or more, a high-hardness resin layer having excellent adhesion to the substrate layer and surface hardness can be obtained. On the other hand, when the content of the (meth)acrylate structural unit (a) is 80 mol% or less, it is not easy to warp due to water absorption of the anti-glare laminate, so it is preferred.
[0095] In addition, the content of the aliphatic vinyl structural unit (b) represented by the general formula (2) is preferably 20 to 35 mol%, more preferably 20 to 30 mol%, relative to the total structural units of the resin (B1) (copolymer resin). When the content of the aliphatic vinyl structural unit (b) is 20 mol% or more, it is preferred because it can prevent warping under high temperature and high humidity. On the other hand, when the content of the aliphatic vinyl structural unit (b) is 35 mol% or less, it is preferred because it can prevent peeling at the interface with the substrate layer.
[0096] The content of the other structural units is preferably 10 mol% or less, more preferably 5 mol% or less, and particularly preferably 2 mol% or less, based on the total structural units of the resin (B1) (copolymer resin).
[0097] In this specification, the "copolymer" may be any structure of a random, block or alternating copolymer.
[0098] The weight average molecular weight of the resin (B1) is not particularly limited, but is preferably 50,000 to 400,000, more preferably 70,000 to 300,000, from the viewpoint of strength and moldability.
[0099] The glass transition temperature of the resin (B1) is preferably 110 to 140°C, more preferably 110 to 135°C, and particularly preferably 110 to 130°C. When the glass transition temperature is 110°C or higher, deformation or cracking of the resin sheet in a hot environment or a hot and humid environment rarely occurs, so it is preferred. On the other hand, when it is 140°C or lower, the processability is excellent during molding by continuous hot molding using a mirror roller or a shaping roller, or by intermittent hot molding using a mirror mold or a shaping mold, so it is preferred. Among them, the glass transition temperature of the present invention is a temperature measured by using a differential scanning calorimeter at a heating rate of 10°C / min on 10 mg of a sample and calculated by the midpoint method.
[0100] Specific examples of the resin (B1) include Optimas 7500 and 6000 (manufactured by Mitsubishi Gas Chemical Co., Ltd.) The resin (B1) may be used alone or in combination of two or more.
[0101] The method for producing the resin (B1) is not particularly limited, and the resin (B1) is preferably obtained by polymerizing at least one (meth)acrylate monomer and at least one aromatic vinyl monomer, and then hydrogenating the aromatic double bonds derived from the aromatic vinyl monomer.
[0102] The aromatic vinyl monomer is not particularly limited, and examples thereof include styrene, α-methylstyrene, p-hydroxystyrene, alkoxystyrene, chlorostyrene, and derivatives thereof. Among them, the aromatic vinyl monomer is preferably styrene.
[0103] The polymerization of the (meth)acrylate monomer and the aromatic vinyl monomer can be carried out by a known method, for example, by bulk polymerization or solution polymerization.
[0104] The bulk polymerization method is carried out by continuously supplying a monomer composition containing the above-mentioned monomers and a polymerization initiator to a complete mixing tank and performing continuous polymerization at 100 to 180° C. The above-mentioned monomer composition may contain a chain transfer agent as necessary.
[0105] The polymerization initiator is not particularly limited, and examples thereof include organic peroxides such as tert-amyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, benzoyl peroxide, 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, tert-hexyl propoxyisopropyl monocarbonate, tert-amyl peroxy-n-octanoate, tert-butyl peroxyisopropyl monocarbonate, and di-tert-butyl peroxide, and azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), and 2,2'-azobis(2,4-dimethylvaleronitrile). These polymerization initiators may be used alone or in combination of two or more.
[0106] The chain transfer agent is not particularly limited, and an example thereof includes α-methylstyrene dimer.
[0107] Examples of the solvent used in the solution polymerization method include hydrocarbon solvents such as toluene, xylene, cyclohexane, and methylcyclohexane, ester solvents such as ethyl acetate and methyl isobutyrate, ketone solvents such as acetone and methyl ethyl ketone, ether solvents such as tetrahydrofuran and dioxane, and alcohol solvents such as methanol and isopropanol. These solvents may be used alone or in combination of two or more.
[0108] The solvent used in the hydrogenation reaction after the polymerization of the (meth)acrylate monomer and the aromatic vinyl monomer may be the same as or different from the above-mentioned polymerization solvent. For example, hydrocarbon solvents such as cyclohexane and methylcyclohexane, ester solvents such as ethyl acetate and methyl isobutyrate, ketone solvents such as acetone and methyl ethyl ketone, ether solvents such as tetrahydrofuran and dioxane, alcohol solvents such as methanol and isopropanol, etc. may be mentioned.
[0109] The resin (B1) can be obtained by polymerizing a (meth)acrylic acid ester monomer and an aromatic vinyl monomer as described above and then hydrogenating the aromatic double bonds derived from the aromatic vinyl monomer.
[0110] The method of hydrogenation is not particularly limited, and a known method can be used. For example, it can be carried out in an intermittent or continuous flow manner at a hydrogen pressure of 3 to 30 MPa and a reaction temperature of 60 to 250° C. When the reaction temperature is above 60° C., it is preferred because the reaction time will not be too long. On the other hand, when the reaction temperature is below 250° C., it is preferred because side reactions such as molecular chain scission or hydrogenation of the ester site will not or will hardly occur.
[0111] Examples of the catalyst used for the hydrogenation reaction include solid catalysts in which metals such as nickel, palladium, platinum, cobalt, ruthenium, rhodium, or oxides, salts, or coordination compounds of these metals are supported on a porous carrier such as carbon, alumina, silica, silica-alumina, diatomaceous earth, or the like.
[0112] Preferably, more than 70% of the aromatic double bonds derived from the aromatic vinyl monomer are hydrogenated by hydrogenation reaction. That is, the unhydrogenated rate of the aromatic double bonds contained in the structural units derived from the aromatic vinyl monomer is preferably less than 30%, more preferably less than 10%, and further preferably less than 5%. When the unhydrogenated rate is less than 30%, it is preferred because a resin with excellent transparency can be obtained. Among them, the structural units of the unhydrogenated part may become other structural units in the resin (B1).
[0113] The resin (B1) may be mixed with other resins within the range that does not impair transparency. That is, the resin (B1) is a resin composition comprising the copolymer and other resins. Examples of the other resins include methyl methacrylate-styrene copolymer resins, polymethyl methacrylate, polystyrene, polycarbonate, cycloolefin (co)polymer resins, acrylonitrile-styrene copolymer resins, acrylonitrile-butadiene-styrene copolymer resins, and various elastomers.
[0114] (Resin (B2))
[0115] The resin (B2) comprises 35 to 65% by mass, preferably 40 to 60% by mass, of the resin (B1) and 35 to 65% by mass, preferably 40 to 60% by mass of a styrene-unsaturated dicarboxylic acid copolymer (C). In addition, the styrene-unsaturated dicarboxylic acid copolymer (C) comprises 65 to 90% by mass of a styrene structural unit (c1) and 10 to 35% by mass of an unsaturated dicarboxylic anhydride structural unit (c2). That is, the resin (B2) is a resin composition comprising two or more resins.
[0116] Resin (B1)
[0117] As the resin (B1), the above-mentioned resins can be used. In this case, the resin (B1) may be used alone or in combination of two or more.
[0118] Styrene-unsaturated dicarboxylic acid copolymer (C)
[0119] The styrene-unsaturated dicarboxylic acid-based copolymer (C) contains a styrene-based structural unit (c1) and an unsaturated dicarboxylic acid anhydride structural unit (c2).
[0120] Styrene structural unit (c1)
[0121] As the styrene monomer, there is no particular limitation, and any known styrene monomer can be used. Specific examples of styrene monomers include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, tert-butylstyrene, etc. Among them, styrene is particularly preferred from the perspective of solubilization. These styrene monomers can be used alone or in combination of two or more.
[0122] The content of the styrene structural unit (c1) is 65 to 90% by mass, preferably 70 to 85% by mass, based on the total mass of the styrene-unsaturated dicarboxylic acid copolymer (C).
[0123] Unsaturated dicarboxylic acid anhydride structural unit (c2)
[0124] The unsaturated dicarboxylic acid anhydride monomer is not particularly limited, and examples thereof include anhydrides of maleic acid, itaconic acid, citraconic acid, aconitic acid, etc. Among them, maleic anhydride is preferred from the perspective of compatibility with styrene monomers. These unsaturated dicarboxylic acid anhydride monomers may be used alone or in combination of two or more.
[0125] The content of the unsaturated dicarboxylic acid anhydride structural unit (c2) is 10 to 35% by mass, preferably 15 to 30% by mass, based on the total mass of the styrene-unsaturated dicarboxylic acid copolymer (C).
[0126] Specific examples of the styrene-unsaturated dicarboxylic acid copolymer (C) include XIBOND140, XIBOND160, XIRAN SO23110, and XIRAN SO26080 (manufactured by Polyscope Co., Ltd.) These styrene-unsaturated dicarboxylic acid copolymers (C) may be used alone or in combination of two or more.
[0127] (Resin (B3))
[0128] The resin (B3) comprises 10 to 55% by mass of a resin (D) containing a vinyl monomer and 45 to 90% by mass of a styrene-unsaturated dicarboxylic acid copolymer (E). In addition, the styrene-unsaturated dicarboxylic acid copolymer (E) comprises 50 to 80% by mass of a styrene structural unit (e1), 10 to 30% by mass of an unsaturated dicarboxylic acid structural unit (e2), and 5 to 30% by mass of a vinyl structural unit (e3). That is, the resin (B3) is a resin composition comprising two or more resins.
[0129] ·Resin containing vinyl monomer (D)
[0130] The resin (D) containing a vinyl monomer is not particularly limited, and examples thereof include homopolymers of vinyl monomers such as acrylonitrile, methacrylonitrile, acrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, and 2-ethylhexyl methacrylate. Among them, the resin (D) containing a vinyl monomer preferably contains methyl methacrylate as a structural unit. The resin (D) containing a vinyl monomer may be a polymer using one of the above structural units, or a copolymer using two or more of the above structural units in combination.
[0131] The weight average molecular weight of the resin (D) containing a vinyl monomer is preferably 10,000 to 500,000, more preferably 50,000 to 300,000.
[0132] The above-mentioned resin (D) containing a vinyl monomer may be used alone or in combination of two or more.
[0133] ·Styrene-unsaturated dicarboxylic acid copolymer (E)
[0134] The styrene-unsaturated dicarboxylic acid copolymer (E) contains a styrene structural unit (e1), an unsaturated dicarboxylic acid anhydride structural unit (e2), and a vinyl structural unit (e3).
[0135] Styrene structural unit (e1)
[0136] As the styrene monomer, there is no particular limitation, and any known styrene monomer can be used. Specific examples of styrene monomers include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, tert-butylstyrene, etc. Among them, styrene is particularly preferred from the perspective of mutual compatibility. These styrene monomers can be used alone or in combination of two or more.
[0137] The content of the styrene structural unit (e1) is 50 to 80% by mass, preferably 50 to 70% by mass, based on the total mass of the styrene-unsaturated dicarboxylic acid copolymer (E).
[0138] Unsaturated dicarboxylic acid anhydride structural unit (e2)
[0139] The unsaturated dicarboxylic acid anhydride monomer is not particularly limited, and examples thereof include anhydrides of maleic acid, itaconic acid, citraconic acid, aconitic acid, etc. Among them, maleic anhydride is preferred from the perspective of compatibility with styrene monomers. These unsaturated dicarboxylic acid anhydride monomers may be used alone or in combination of two or more.
[0140] The content of the unsaturated dicarboxylic acid anhydride structural unit (e2) is 10 to 30% by mass, preferably 10 to 25% by mass, based on the total mass of the styrene-unsaturated dicarboxylic acid copolymer (E).
[0141] · Vinyl structural unit (e3)
[0142] As the vinyl monomer, there is no particular limitation, and examples thereof include acrylonitrile, methacrylonitrile, acrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate and the like. Among them, methyl methacrylate (MMA) is preferred from the perspective of compatibility with the resin (D) containing the vinyl monomer. These vinyl monomers may be used alone or in combination of two or more.
[0143] The content of the vinyl structural unit (e3) is 5 to 30% by mass, preferably 7 to 27% by mass, based on the total mass of the styrene-unsaturated dicarboxylic acid copolymer (E).
[0144] The weight average molecular weight of the styrene-unsaturated dicarboxylic acid copolymer (E) is preferably 50000 to 200000, more preferably 80000 to 200000. The weight average molecular weight within the above range is preferred because the compatibility with the resin (D) containing a vinyl monomer is good and the effect of improving heat resistance is excellent.
[0145] Specific examples of the styrene-unsaturated dicarboxylic acid copolymer (E) include, but are not limited to, RESISFY R100, R200, R310 (manufactured by Denki Kagaku Kogyo Co., Ltd.), Delpet 980N (manufactured by Asahi Kasei Corporation), etc. The styrene-unsaturated dicarboxylic acid copolymer (E) may be used alone or in combination of two or more.
[0146] (Resin (B4))
[0147] The resin (B4) is a resin copolymer (G) containing 5 to 20% by mass of a styrene structural unit, 60 to 90% by mass of a (meth)acrylate structural unit, and 5 to 20% by mass of an N-substituted maleimide structural unit, or an alloy of the resin copolymer (G) and a styrene-unsaturated dicarboxylic acid copolymer (E).
[0148] ·Resin copolymer (G)
[0149] The resin copolymer (G) contains a styrene structural unit, a (meth)acrylate structural unit and an N-substituted maleimide structural unit.
[0150] Styrene structural unit
[0151] As the styrene monomer, there is no particular limitation, and any known styrene monomer can be used. Specific examples of styrene monomers include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, tert-butylstyrene, etc. Among them, styrene is particularly preferred from the perspective of mutual compatibility. These styrene monomers can be used alone or in combination of two or more.
[0152] The content of the styrene structural unit is 5 to 20% by mass, preferably 5 to 15% by mass, and more preferably 5 to 10% by mass, based on the total mass of the resin (B4) (resin copolymer (G)).
[0153] (Meth)acrylate structural unit
[0154] The (meth)acrylate monomer is not particularly limited, and examples thereof include acrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, etc. Among them, methyl methacrylate is preferred. These (meth)acrylate monomers may be used alone or in combination of two or more.
[0155] The content of the (meth)acrylate structural unit is 60 to 90% by mass, preferably 70 to 90% by mass, and more preferably 80 to 90% by mass, based on the total mass of the resin (B4) (resin copolymer (G)).
[0156] N-substituted maleimide structural unit
[0157] As the N-substituted maleimide monomer, there is no particular limitation, and examples thereof include N-phenylmaleimide, N-chlorophenylmaleimide, N-methylphenylmaleimide, N-naphthylmaleimide, N-hydroxyphenylmaleimide, N-methoxyphenylmaleimide, N-carboxyphenylmaleimide, N-nitrophenylmaleimide, N-tribromophenylmaleimide and other N-arylmaleimides. Among them, N-phenylmaleimide is preferred from the perspective of compatibility with the (meth)acrylic acid structural unit. Furthermore, these N-substituted maleimide monomers may be used alone or in combination of two or more.
[0158] The content of the N-substituted maleimide structural unit is 5 to 20% by mass, preferably 5 to 15% by mass, and more preferably 5 to 10% by mass, based on the total mass of the resin (B4) (resin copolymer (G)).
[0159] The weight average molecular weight of the resin copolymer (G) is preferably 50,000 to 250,000, more preferably 100,000 to 200,000.
[0160] Specific examples of the resin copolymer (G) include Delpet PM120N (manufactured by Asahi Kasei Chemicals Corporation), but the present invention is not limited to this.
[0161] The method for producing the resin copolymer (G) is not particularly limited, and the resin copolymer (G) can be produced by solution polymerization, bulk polymerization, or the like.
[0162] Polymer alloy
[0163] The polymer alloy is a polymer alloy of the resin copolymer (G) and the styrene-unsaturated dicarboxylic acid copolymer (E).
[0164] In this case, the resin copolymer (G) and the styrene-unsaturated dicarboxylic acid copolymer (E) are preferably alloys of polymers having high glass transition temperatures.
[0165] The method for producing the polymer alloy is not particularly limited, and examples thereof include a method of using a twin-screw extruder having a screw diameter of 26 mm, performing melt kneading at a barrel temperature of 240° C., extruding into a strand form, and then granulating using a granulator.
[0166] (Resin (B5))
[0167] The resin (B5) contains a structural unit (H) represented by the following formula (3). The resin (B5) is preferably a copolymer further containing a structural unit (J) represented by the following formula (4). The above copolymer may further contain other structural units.
[0168]
[0169] The content of the structural unit (H) represented by the formula (3) is preferably 50 to 100 mol %, more preferably 60 to 100 mol %, and even more preferably 70 to 100 mol % based on all the structural units of the resin (B5).
[0170]
[0171] The content of the structural unit (J) represented by the formula (4) is preferably 0 to 50 mol %, more preferably 0 to 40 mol %, and even more preferably 0 to 30 mol % based on all the structural units of the resin (B5).
[0172] The content of other structural units is preferably 10 mol% or less, more preferably 5 mol% or less, particularly preferably 2 mol% or less, based on all structural units of the resin (B5).
[0173] The total content of the structural unit (H) and the structural unit (J) is preferably 90 to 100 mol %, more preferably 95 to 100 mol %, and even more preferably 98 to 100 mol % based on all the structural units of the resin (B5).
[0174] The weight average molecular weight of the resin (B5) is preferably 15,000 to 75,000, more preferably 20,000 to 70,000, particularly preferably 25,000 to 65,000.
[0175] Specific examples of the resin (B5) include IUPILON KH3410UR, KH3520UR, and KS3410UR (manufactured by Mitsubishi Engineering-Plastics Corporation), but the present invention is not limited thereto. The above resin (B5) may be used alone or in combination of two or more.
[0176] The method for producing the resin (B5) is not particularly limited, and the resin (B5) can be produced by the same method as the method for producing the polycarbonate resin (a1) except that bisphenol C is used as a monomer.
[0177] (Resin (B6))
[0178] The resin (B6) comprises 35 to 65% by mass of a resin (D) containing a vinyl monomer and 35 to 65% by mass of a styrene-unsaturated dicarboxylic acid copolymer (C). In addition, the styrene-unsaturated dicarboxylic acid copolymer (C) comprises 65 to 90% by mass of a styrene structural unit (c1) and 10 to 35% by mass of an unsaturated dicarboxylic anhydride structural unit (c2). That is, the resin (B6) is a resin composition comprising two or more resins.
[0179] ·Resin containing vinyl monomer (D)
[0180] As the resin (D) containing a vinyl monomer, the same resins as those described above for the resin (B3) can be used. The resin (D) containing a vinyl monomer can be used alone or in combination of two or more.
[0181] Styrene-unsaturated dicarboxylic acid copolymer (C)
[0182] As the styrene-unsaturated dicarboxylic acid copolymer (C), the same copolymers as those described above for the resin (B2) can be used. The styrene-unsaturated dicarboxylic acid copolymer (C) can be used alone or in combination of two or more.
[0183] By containing at least one selected from the resins (B1) to (B6) as the high-hardness resin, an anti-glare laminate having more excellent shape stability under high temperature and high humidity can be obtained, which is preferred.
[0184] [additive]
[0185] The high hardness resin layer may contain additives.
[0186] As the above-mentioned additive, there is no particular restriction, and substances commonly used in the anti-glare laminate can be used. As specific examples, antioxidants, anti-coloring agents, antistatic agents, release agents, lubricants, dyes, pigments, plasticizers, flame retardants, resin modifiers, solubilizers, reinforcing materials such as organic fillers or inorganic fillers can be enumerated.
[0187] The amount of the additive is preferably 0 to 10% by mass, more preferably 0 to 7% by mass, and particularly preferably 0 to 5% by mass, based on the total mass of the high-hardness resin layer.
[0188] The method for mixing the additives and the resin is not particularly limited, and a total amount blending method, a masterbatch dry blending method, a total amount dry blending method, etc. may be used.
[0189] [Constitution of high hardness resin layer]
[0190] The thickness of the high hardness resin layer is preferably 10 to 250 μm, more preferably 30 to 200 μm, and particularly preferably 60 to 150 μm. When the thickness of the high hardness resin layer is 10 μm or more, it is preferred because the surface hardness is improved. On the other hand, when the thickness of the high hardness resin layer is 250 μm or less, it is preferred because the impact resistance is improved.
[0191] [Lamination of high hardness resin layer and base material layer]
[0192] As described above, another layer may be present between the base layer and the high hardness resin layer, but here, the case where the high hardness resin layer is laminated on the base layer will be described.
[0193] The total thickness of the substrate layer and the high hardness resin layer is preferably 100 μm to 3500 μm, more preferably 100 μm to 3000 μm, further preferably 500 μm to 3000 μm, and particularly preferably 1200 to 3000 μm. When the total thickness is 100 μm or more, it is preferred because the rigidity of the sheet can be ensured. On the other hand, when the total thickness is 3500 μm or less, it is preferred because the sensitivity of the touch sensor can be prevented from being deteriorated when a touch panel is provided under the sheet.
[0194] The ratio of the thickness of the substrate layer to the total thickness of the substrate layer and the high hardness resin layer is preferably 75% to 99%, more preferably 80% to 99%, and particularly preferably 85% to 99%. By setting it within the above range, both hardness and impact resistance can be achieved.
[0195] The method of laminating the high hardness resin layer on the substrate layer is not particularly limited, and examples thereof include a method of laminating a separately formed substrate layer and a high hardness resin layer and heat-pressing the two; a method of laminating a separately formed substrate layer and a high hardness resin layer and bonding the two with a bonding agent; a method of co-extruding the substrate layer and the high hardness resin layer; a method of insert-molding and integrating the substrate layer on a pre-formed high hardness resin layer, etc. Among them, co-extrusion molding is preferred from the perspective of manufacturing cost and productivity.
[0196] The co-extrusion method is not particularly limited. For example, in the feed block method, a high-hardness resin layer is arranged on one side of the substrate layer using a feed block, and after extruding into a sheet using a T-die, it is cooled while passing through a molding roller to form a desired laminate. In addition, in the multi-flow method, a high-hardness resin layer is arranged on one side of the substrate layer in a multi-flow die, and after extruding into a sheet, it is cooled while passing through a molding roller to form a desired laminate.
[0197] <Hard Coating>
[0198] The hard coating layer is not particularly limited, but is preferably an acrylic hard coating layer. In this specification, "acrylic hard coating layer" refers to a coating film having a cross-linked structure formed by polymerizing a monomer, oligomer or prepolymer containing a (meth)acryloyl group as a polymerizable group. In addition, the hard coating layer may further contain a UV absorber.
[0199] The hard coating preferably does not contain organic particles and inorganic particles. By not containing organic particles and inorganic particles, scratch resistance can be improved. In addition, as described later, by using a transfer of a mold to carry out anti-glare treatment of the hard coating, a hard coating having a concavo-convex shape but not containing organic particles and inorganic particles can be formed.
[0200] The content of the (meth)acrylic acid monomer is preferably 2 to 98% by mass, more preferably 5 to 50% by mass, and even more preferably 20 to 40% by mass, based on the total mass of the (meth)acrylic acid monomer, the (meth)acrylic acid oligomer, and the surface modifier.
[0201] The content of the (meth)acrylic oligomer is preferably 2 to 98% by mass, more preferably 50 to 95% by mass, and even more preferably 60 to 80% by mass based on the total mass of the (meth)acrylic monomer, the (meth)acrylic oligomer, and the surface modifier.
[0202] The content of the surface modifier is preferably 0 to 15% by mass, more preferably 1 to 10% by mass, and even more preferably 2 to 5% by mass, based on the total mass of the (meth)acrylic monomer, the (meth)acrylic oligomer, and the surface modifier.
[0203] In addition, when a photopolymerization initiator is included, the content of the photopolymerization initiator is preferably 0.001 to 7 parts by mass, more preferably 0.01 to 5 parts by mass, and even more preferably 0.1 to 3 parts by mass relative to 100 parts by mass of the total of the (meth)acrylic monomer, the (meth)acrylic oligomer, and the surface modifier. In this specification, the photopolymerization initiator refers to a photo radical generator.
[0204] [(Meth)acrylic acid monomer]
[0205] As the (meth)acrylic monomer, any monomer having a (meth)acryloyl group as a functional group in the molecule can be used, and specific examples thereof include monofunctional monomers, difunctional monomers, and trifunctional or higher-functional monomers.
[0206] Examples of the monofunctional monomer include (meth)acrylic acid and (meth)acrylate esters.
[0207] Specific examples of difunctional and / or trifunctional (meth)acrylic monomers include diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, tetraethylene glycol di(meth)acrylate, hydroxyvaleric acid neopentyl glycol diacrylate, neopentyl glycol di(meth)acrylate, 1,4-butylene glycol diacrylate, 1,3-butylene glycol di(meth)acrylate, di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate. dicyclopentadienyl diacrylate, polyethylene glycol diacrylate, 1,4-butanediol oligoacrylate, neopentyl glycol oligoacrylate, 1,6-hexanediol oligoacrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxy tri(meth)acrylate, trimethylolpropane propoxy tri(meth)acrylate, pentaerythritol tri(meth)acrylate, glycerol propoxy tri(meth)acrylate, trimethylolpropane trimethacrylate, trimethylolpropane ethylene oxide addition triacrylate, glycerol propylene oxide addition triacrylate, pentaerythritol tetraacrylate, etc.
[0208] The hard coat layer may contain one or two or more (meth)acrylic monomers.
[0209] [(Meth)acrylic acid oligomer]
[0210] Examples of the (meth)acrylic oligomer include difunctional or higher polyfunctional urethane (meth)acrylate oligomers (hereinafter also referred to as “polyfunctional urethane (meth)acrylate oligomers”), difunctional or higher polyfunctional polyester (meth)acrylate oligomers (hereinafter also referred to as “polyfunctional polyester (meth)acrylate oligomers”), and difunctional or higher polyfunctional epoxy (meth)acrylate oligomers (hereinafter also referred to as “polyfunctional epoxy (meth)acrylate oligomers”).
[0211] Examples of the polyfunctional urethane (meth)acrylate oligomer include a reaction product of an amination reaction between a (meth)acrylate monomer having at least one (meth)acryloyloxy group and a hydroxyl group in one molecule and a polyisocyanate; a reaction product of an amination reaction between an isocyanate compound obtained by reacting a polyol with a polyisocyanate and a (meth)acrylate monomer having at least one (meth)acryloyloxy group and a hydroxyl group in one molecule; and the like.
[0212] Examples of the (meth)acrylate monomer having at least one (meth)acryloyloxy group and hydroxyl group in one molecule used in the amination reaction include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, glycerol di(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol penta(meth)acrylate.
[0213] Examples of the polyisocyanate used in the amination reaction include hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, toluene diisocyanate, xylene diisocyanate, diisocyanates obtained by hydrogenating aromatic isocyanates among these isocyanates (for example, diisocyanates such as hydrogenated toluene diisocyanate and hydrogenated xylene diisocyanate), polyisocyanates of diisocyanates or triisocyanates such as triphenylmethane triisocyanate and dimethylene triphenyl triisocyanate, or polyisocyanates obtained by polymerizing diisocyanates.
[0214] As the polyols used for the urethanization reaction, in addition to conventional aromatic, aliphatic and alicyclic polyols, polyester polyols, polyether polyols and the like can be used.
[0215] Examples of the aliphatic and alicyclic polyols generally include 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, ethylene glycol, propylene glycol, trimethylolethane, trimethylolpropane, dimethylolheptane, dimethylolpropionic acid, dimethylolbutyric acid, glycerin, and hydrogenated bisphenol A.
[0216] As polyester polyols, products obtained by dehydration condensation reaction of the above-mentioned polyols and polycarboxylic acids can be cited. As specific compounds of polycarboxylic acids, succinic acid, adipic acid, maleic acid, trimellitic acid, hexahydrophthalic acid, phthalic acid, isophthalic acid, terephthalic acid, etc. can be cited. These polycarboxylic acids can also be anhydrides.
[0217] Examples of the polyether polyol include, in addition to polyalkylene glycol, polyoxyalkylene-modified polyols obtained by reacting the above-mentioned polyols or phenols with an alkylene oxide.
[0218] The above-mentioned multifunctional polyester (meth) acrylate oligomer is obtained by a dehydration condensation reaction using (meth) acrylic acid, a polycarboxylic acid and a polyol. As the polycarboxylic acid used in the dehydration condensation reaction, succinic acid, adipic acid, maleic acid, itaconic acid, trimellitic acid, pyromellitic acid, hexahydrophthalic acid, phthalic acid, isophthalic acid, terephthalic acid, etc. can be cited. These polycarboxylic acids can also be anhydrides. In addition, as the polyol used in the dehydration condensation reaction, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, triethylene glycol, propylene glycol, neopentyl glycol, dimethylol heptane, dimethylol propionic acid, dimethylol butyric acid, trimethylol propane, di(trimethylol) propane, pentaerythritol, dipentaerythritol, etc. can be cited.
[0219] The polyfunctional epoxy (meth)acrylate oligomer is obtained by addition reaction of polyglycidyl ether and (meth)acrylic acid. Examples of polyglycidyl ether include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and bisphenol A diglycidyl ether.
[0220] The hard coat layer may contain one or two or more (meth)acrylic oligomers.
[0221] [Surface modifier]
[0222] Surface modifiers refer to substances such as leveling agents, antistatic agents, surfactants, water-repellent and oil-repellent agents, inorganic particles, and organic particles that can change the surface properties of the hard coating.
[0223] Examples of the leveling agent include polyether-modified polyalkylsiloxane, polyether-modified silicone, polyester-modified hydroxyl-containing polyalkylsiloxane, polyether-modified polydimethylsiloxane having an alkyl group, modified polyether, and silicon-modified acrylic compounds.
[0224] Examples of the antistatic agent include glycerin fatty acid ester monoglyceride, glycerin fatty acid ester organic acid monoglyceride, polyglycerin fatty acid ester, sorbitan fatty acid ester, cationic surfactants, and anionic surfactants.
[0225] Examples of the surfactant and the water- and oil-repellent agent include fluorinated surfactants and water- and oil-repellent agents such as oligomers having a fluorinated group and a lipophilic group and oligomers having a fluorinated group, a hydrophilic group, a lipophilic group and a UV reactive group.
[0226] Examples of the inorganic particles include silica particles, alumina particles, zirconia particles, silver particles, and glass particles.
[0227] Examples of the organic particles include acrylic compound particles and silicon particles.
[0228] The hard coating layer may contain one or two or more surface modifiers.
[0229] [Photopolymerization initiator]
[0230] As the photopolymerization initiator, a monofunctional photopolymerization initiator can be cited. Specifically, 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone (Darocure-2959, manufactured by Merck), α-hydroxy-α,α'-dimethylacetophenone (Darocure-1173, manufactured by Merck), methoxyacetophenone, 2,2'-dimethoxy-2-phenylacetophenone (Irgacure-651), 1-hydroxy-cyclohexylphenylketone and other acetophenone-based initiators, benzoin ethyl ether, benzoin isopropyl ether and other benzoin ether-based initiators, as well as halogenated ketones, acylphosphine oxides, acylphosphonates, etc. can be exemplified. These photopolymerization initiators can be used alone or in combination of two or more.
[0231] [UV absorber]
[0232] Examples of the UV absorber include hydroxyphenyltriazine-based, benzotriazole-based, and benzophenone-based compounds. The UV absorber may be used alone or in combination of two or more.
[0233] [Composition of hard coating]
[0234] The film thickness of the hard coating is preferably 1 to 40 μm, more preferably 2 to 10 μm. When the film thickness of the hard coating is 1 μm or more, it is preferred because sufficient hardness can be obtained. On the other hand, when the film thickness of the hard coating is 40 μm or less, it is preferred because cracks can be suppressed during bending. The film thickness of the hard coating can be measured by observing the cross section with a microscope or the like and measuring the actual length from the coating interface to the surface.
[0235] The pencil hardness of the hard coating surface is preferably HB or more, more preferably H or more, further preferably 2H or more, and particularly preferably 2H to 3H. The pencil hardness of the hard coating is the evaluation result of the pencil scratch hardness test according to JIS K 5600-5-4: 1999. Specifically, a pencil is pressed on the surface of the hard coating at an angle of 45 degrees and a load of 750 g, and the hardness is gradually increased. The hardness of the hardest pencil that does not cause a scratch is evaluated as the pencil hardness.
[0236] By having a concavoconvex shape on the hard coat layer, an anti-glare laminate having excellent anti-glare properties and tactile comfort can be obtained. Specifically, the interface expansion area ratio (Sdr), arithmetic mean height (Sa) and autocorrelation length (Sal) of the hard coat layer satisfy the following formulas (i) to (iii). In this specification, the interface expansion area ratio (Sdr), arithmetic mean height (Sa) and autocorrelation length (Sal) are measured in accordance with ISO 25178-2:2012 as described in the examples described later.
[0237] 0≤Sdr≤0.6 (i)
[0238] 0≤Sa≤0.16 (ii)
[0239] 0≤Sal≤15.0 (iii)
[0240] Regarding the above formula (i), the interface expansion area ratio (Sdr) is an indicator of anti-glare properties and is related to haze. When Sdr exceeds 0.6, the light scattering degree is too high to cause whitening and the texture is also deteriorated. It is more preferred that formula (i) satisfies 0≤Sdr≤0.5, further preferably satisfies 0≤Sdr≤0.4, and particularly preferably satisfies 0≤Sdr≤0.3.
[0241] Regarding the above formula (ii), the arithmetic mean height (Sa) is an indicator of anti-glare properties and is related to imaging properties. When Sa exceeds 0.16, the light scattering degree is too high to cause whitening and the texture is also deteriorated. Formula (ii) more preferably satisfies 0.01≤Sa≤0.15, further preferably satisfies 0.02≤Sa≤0.14, and particularly preferably satisfies 0.03≤Sa≤0.13.
[0242] Regarding the above formula (iii), the autocorrelation length (Sal) is an indicator of anti-glare properties and is related to glare. In high-definition display devices with fine pixel sizes, the existing surface unevenness size leads to reduced image quality such as glare or blurred text. That is, in the case of high-definition display devices, the surface unevenness size is close to the pixel size of high-definition display in the order of magnitude, and glare occurs under the lens effect brought about by the surface unevenness. Under the previous particle size, the scattering near the transmitted light propagating in a straight line increases, the pixel outline becomes unclear, and the text is blurred. Moreover, since the intensity distribution of the transmitted scattered light depends on the size of the added particles, when the particle size is smaller, the scattering around the transmitted light propagating in a straight line decreases, and the glare is also reduced; and when the particle size is larger, the scattering near the transmitted light propagating in a straight line increases, resulting in glare. When Sal exceeds 15.0, the scattering near the transmitted light propagating in a straight line increases, and the glare increases. Formula (iii) more preferably satisfies 1.0≤Sal≤12.0, further preferably satisfies 2.0≤Sal≤10.0, and particularly preferably satisfies 3.0≤Sal≤8.0.
[0243] <Haze>
[0244] The haze of the hard coat layer of the anti-glare laminate of the present invention is preferably 30% or less, more preferably 25% or less, further preferably 22% or less, and particularly preferably 21%. In this specification, the haze is a value measured using HR-100 (Murakami Color Research Laboratory) in accordance with JIS K 7136:2000.
[0245] <Glare>
[0246] The glare in the hard coating layer of the anti-glare laminate of the present invention is preferably 8% or less, more preferably 7% or less, further preferably 6% or less, and particularly preferably 5% or less. In this specification, the anti-glare laminate is set on a 265ppi iPad6 (registered trademark) displaying green (R: 0, G: 205, B: 0) in a concave-convex shape facing upward, and the image is captured using the Prometric Y29 manufactured by Konica Minolta. 60mm×60mm is cut out from the captured image, and the randomly distributed cloud spot sequence (Random Mura Sequence) of the analysis software "True Test" is used to divide the cut image into nine parts, and the glare value is calculated in each area of the nine parts by "(display) brightness standard deviation / average brightness of the evaluation range". When used as a front panel, the average value of the glare value calculated for each of the nine areas is preferably less than 2.0. The distance between the lens and the anti-glare laminate is set to 500mm.
[0247] Glare value calculation method: (display) brightness standard deviation / average brightness of the evaluation range
[0248] <Imageability>
[0249] As an evaluation method for image reflection, the image clarity (imaging property) of reflection measured at an incident angle of 60° based on JIS K7374 can be cited. The optical comb width is 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm. Since the numerical deviation is large when the optical comb width is narrow and the numerical deviation is small when the optical comb width is wide, the optical comb width is preferably 2.0 mm.
[0250] The reflection clarity measured under the condition of a light incident angle of 60° shows that the larger the value, the easier it is for the image to be reflected, and the smaller the value, the less likely it is for the image to be reflected. In the present invention, the reflection clarity can be measured by the method described in the examples described below.
[0251] In order to achieve both blurring of text and reflection performance, the reflection clarity of the concavoconvex shape in the present invention measured at an incident angle of 60° using a 2.0 mm wide optical comb is preferably 15% or more, more preferably 40% or more, and particularly preferably 50% or more.
[0252] [Method for forming hard coat layer]
[0253] The method for forming the hard coat layer is not particularly limited, and the hard coat layer may be formed, for example, by applying a hard coat liquid on a layer (eg, a high-hardness resin layer) below the hard coat layer and then performing photopolymerization.
[0254] The coating method of the hard coating liquid (polymerizable composition, reactive composition) is not particularly limited, and a known method can be used, for example, spin coating, dip coating, spray coating, slide coating, rod coating, roll coating, gravure coating, meniscus coating, flexographic printing, screen printing, beat coating, brush coating, etc.
[0255] As the lamp used for light irradiation during photopolymerization, a lamp having a light emission distribution below 420 nm in wavelength can be used. As examples thereof, low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, chemical lamps, black light lamps, microwave-excited mercury lamps, metal halide lamps, etc. can be cited. Among them, high-pressure mercury lamps or metal halide lamps can efficiently emit light in the active wavelength region of the photopolymerization initiator, and will not emit a large amount of short-wavelength light that reduces the viscoelastic properties of the obtained polymer due to crosslinking or long-wavelength light that heats and evaporates the reaction composition, so they are preferred.
[0256] The irradiation intensity of the above lamp is a factor that affects the polymerization degree of the obtained polymer and can be appropriately controlled according to the various properties of the target product. In the case of a conventional cleavage-type photopolymerization initiator having an acetophenone group, the irradiation intensity is preferably 0.1 to 300 mW / cm 2 It is particularly preferred to use a metal halide lamp and set the illumination to 10 to 40 mW / cm 2 .
[0257] Photopolymerization is inhibited by oxygen in the air or oxygen dissolved in the reactive composition. Therefore, it is necessary to implement light irradiation by a method that can eliminate the inhibition of oxygen on the reaction. As one of such methods, there is a film made of polyethylene terephthalate or TEFLON (registered trademark) covering the reactive composition to block contact with oxygen, so that light penetrates the film and irradiates the reactive composition. In addition, it is also possible to irradiate light to the reactive composition through a translucent window in an inert environment where oxygen is replaced by an inert gas such as nitrogen or carbon dioxide.
[0258] When light irradiation is performed under an inert environment, a certain amount of inert gas is always introduced to ensure that the oxygen concentration in the environment is at a low level. Due to the introduction of the inert gas, an airflow is generated on the surface of the reactive composition, resulting in evaporation of the monomer. In order to control the evaporation level of the monomer, the airflow velocity of the inert gas is preferably set to 1 m / sec or less, more preferably to 0.1 m / sec or less relative to the relative velocity of the laminate coated with the hard coating liquid moving under the inert gas environment. By setting the airflow velocity within the above range, the evaporation of the monomer caused by the airflow can be substantially curbed.
[0259] In order to improve the adhesion of the hard coating, the coating surface is sometimes pre-treated. Examples of treatments include sandblasting, solvent treatment, corona discharge treatment, chromic acid treatment, flame treatment, hot air treatment, ozone treatment, ultraviolet treatment, and primer treatment using a resin composition.
[0260] As a method for forming concavoconvex on hard coating (anti-glare treatment), there is no particular restriction, and a method using a mold is preferred. For example, first a high hardness resin layer, a coating film obtained by applying a reactive composition, and a mold are laminated in sequence. Then, the reactive composition is photopolymerized, and then the mold is demoulded. The photopolymer (hard coating) of the reactive composition forms a shape having a rough surface reflecting the mold on its contact surface with the mold. That is, the anti-glare treatment of the hard coating is a method performed by transfer using a mold.
[0261] As long as the mold can transmit ultraviolet light, there is no particular limitation, and glass, transparent resin, etc. can be used. In one embodiment, the mold can include a mold formed by laminating a transparent film and a transparent resin with a rough surface. As the transparent film, a PET film can be mentioned. As the transparent resin with a rough surface, an acrylic resin, etc. can be mentioned. At this time, the rough surface of the transparent resin is not particularly limited, and can be formed by adding particles (organic particles, inorganic particles, etc.) to the transparent resin, or by etching the transparent resin, or by printing the transparent resin and curing it. The shape of the rough surface is not particularly limited, and a pattern is preferred from the perspective of being used for liquid crystal panels and the like. The surface (concave and convex shape) of the hard coating layer can be controlled by controlling the type of mold used (material, surface haze, thickness, shape, etc.), the amount of particles added, etc. Thus, a hard coating layer satisfying the above formulas (i) to (iii) can be formed. In addition, it is preferred that a hard coating layer satisfying the above formulas (iv) to (vi) can be formed.
[0262] In the method for forming the hard coating layer, it is preferred to crimp a PET film with a pattern to transfer the concave-convex shape. That is, according to one embodiment of the present invention, a method for manufacturing an anti-glare laminate is provided. At this time, the manufacturing method includes a step of crimping a PET film with a pattern on the surface of the hard coating layer and transferring the concave-convex shape. Among them, as the patterned PET film, for example, PTH, PTHA or PTHZ of EMBLET manufactured by Unitika Co., Ltd., and PF11 or PF23 of low-glare AG film manufactured by Daicel Co., Ltd. can be used.
[0263] An example of a method for preparing a patterned PET film preferably used in the method for manufacturing the anti-glare laminate of the present invention is to coat a coating liquid on a PET (polyethylene terephthalate) film to a dry film thickness of 2.0 to 4.0 μm, dry the film at 70 to 90° C. for 1 to 3 minutes, and then use a conveyor belt equipped with a high-pressure mercury lamp with a light source distance of 12 cm and a power of 80 W / cm to irradiate the film with ultraviolet rays for curing at a line speed of 1.0 to 3.0 m / min to prepare a patterned PET film.
[0264] The coating solution preferably contains an organic solvent such as methyl ethyl ketone (MEK), an acrylic ultraviolet curable resin, silica particles, and a photoinitiator. As the content of these components, preferably, the organic solvent such as methyl ethyl ketone (MEK) is 70 to 80 parts by mass, the acrylic ultraviolet curable resin is 19 to 29 parts by mass, the silica particles (average particle size 3.5 to 5.0 μm) are 0.2 to 1.0 parts by mass, and the photoinitiator is 2.0 to 4.0 parts by mass. Thus, a hard coating layer satisfying the above formulas (i) to (iii) can be formed.
[0265] <Physical Properties of Anti-Glare Laminated Body>
[0266] In one embodiment, the anti-glare laminate preferably has high shape stability. Specifically, it is preferred that the warpage change after being kept for 120 hours under an environment of a temperature of 85°C and a relative humidity of 85% is less than 350 μm, more preferably less than 250 μm, further preferably less than 175 μm, and particularly preferably less than 75 μm. When the warpage change is less than 350 μm, it is preferred because it is applicable even under a high temperature and high humidity environment. Among them, high shape stability can be achieved by using a high hardness resin layer. By having a high hardness resin layer between the substrate layer and the hard coating layer, the shape of the anti-glare laminate is stable even under a high temperature and high humidity environment. In addition, the shape stability can also be controlled by appropriately changing the materials of the substrate layer and the hard coating layer, the difference in glass transition temperature (Tg) between the substrate layer and the high hardness resin layer, the difference in hardness, the difference in glass transition temperature (Tg) between the high hardness resin layer and the hard coating layer, the difference in hardness, etc.
[0267] <Purpose>
[0268] The anti-glare laminate of the present invention has excellent anti-glare properties and tactile comfort, and therefore can be used as a protective plate or front panel of a liquid crystal surface as described above. In one embodiment, a vehicle-mounted display device comprising an anti-glare laminate is provided. In addition, in another embodiment, a touch panel front protective plate comprising an anti-glare laminate is provided. Moreover, in yet another embodiment, a front panel for OA equipment, a portable electronic device, or a television is provided.
[0269] Example
[0270] Examples of the present invention are given below, but the present invention is not limited to the examples.
[0271] <Measurement of surface roughness>
[0272] The interface extension area ratio (Sdr), arithmetic mean height (Sa) and autocorrelation length (Sal) of the surface of the hard coating layer having an uneven surface were measured using an Olympus Corporation laser scanning confocal microscope "OLS 5000" under the following conditions in accordance with ISO 25178-2:2012.
[0273] [Interface extension area ratio (Sdr)]
[0274] Observation conditions
[0275] Objective lens: 20 times
[0276] Sampling mode: Accuracy first
[0277] Measuring area: 645μm×645μm
[0278] Analysis conditions
[0279] Correction: Remove spike noise, eliminate tilt
[0280] [Arithmetic mean altitude (Sa)]
[0281] Observation conditions
[0282] Objective lens: 20 times
[0283] Sampling mode: Accuracy first
[0284] Measuring area: 645μm×645μm
[0285] Analysis conditions
[0286] Correction: Remove spike noise, eliminate tilt
[0287] [Autocorrelation length (Sal)]
[0288] Observation conditions
[0289] Objective lens: 100x
[0290] Sampling mode: Precision first
[0291] Measuring area: 129μm × 129μm
[0292] Analysis conditions
[0293] Calibration: Remove spike noise, eliminate tilt
[0294] <Haze>
[0295] Use "HR-100" manufactured by Murakami Color Technology Research Institute, and calculate the haze according to the method specified in JIS K 7136:2000
[0296] <Reflectance clarity (imageability)>
[0297] Use "ICM 1T" manufactured by SUGAKIKAI KOGYO CO., LTD., and measure based on JIS K7374 with the anti-glare laminate set so that the transmission direction is parallel to the teeth direction of the light comb. The reflectance image clarity measured under the conditions of using a 2.0mm light comb in the light comb and an incident light angle of 60° is used as the reflectance clarity. Measure in a state where back reflection is suppressed by pasting black tape (black vinyl tape model 117BLA manufactured by 3M Japan Co., Ltd.) on the back of the uneven surface
[0298] <Glare>
[0299] Set the anti-glare laminate on the iPad6 (registered trademark) with 265ppi showing green (R: 0, G: 205, B: 0) with the uneven shape facing up. After taking an image using Prometric Y29 manufactured by Konica Minolta, cut out 60mm × 60mm from the captured image, and use the random distribution cloud pattern sequence (Random Mura Sequence) of the analysis software "True Test" to divide the cut-out image into nine parts. Calculate the glare value in each of the nine divided areas by "(monitor) brightness standard deviation / average brightness of the evaluation range". When used as the front panel, the average value of the glare values calculated for each of the nine areas is preferably 2.0 or less. The distance between the lens and the anti-glare laminate is set to 500mm
[0300] · Calculation method of glare value: (monitor) brightness standard deviation / average brightness of the evaluation range
[0301] <SW hardness>
[0302] On the hard coat layer having the uneven shape of the anti-glare laminate, #0000 steel wool manufactured by NIHON STEEL WOOL Co., Ltd. was used to form a 3D image at 100 gf / cm 2 The test piece was reciprocated 15 times under a load of 10000 and scratched. The degree of damage was visually observed and evaluated in 10 grades. The grades were recorded as RANK1 to RANK10. The test was performed twice, and when the results were different, the range between them was used as the test result.
[0303] RANK1: No scratches (same as inorganic glass);
[0304] RANK2: 1 to 5 scars;
[0305] RANK3: 6 to 10 scars;
[0306] RANK4: 11 to 15 scars;
[0307] RANK5: 16-20 scars;
[0308] RANK6: 21 to 25 scars;
[0309] RANK7: 26-30 scars;
[0310] RANK8: 31-40 scars;
[0311] RANK9: more than 41 scars (same as polymethacrylic acid);
[0312] RANK10: 41 or more scratches (same as polycarbonate).
[0313] <Shape stability>
[0314] The test piece (anti-glare laminate) was cut into 100mm×60mm. The cut test piece was placed on a two-point support type bracket, placed in an environmental testing machine with a temperature of 23% and a relative humidity of 50% for more than 24 hours for state conditioning, and then the warpage (before processing) was measured. Next, the test piece was placed on a bracket, placed in an environmental testing machine with a temperature of 85°C and a relative humidity of 85%, and kept in this state for 120 hours. It was then moved together with the bracket to an environmental testing machine with a temperature of 23% and a relative humidity of 50%, and after being kept in this state for 4 hours, the warpage (after processing) was measured again. The warpage was measured using a three-dimensional shape measuring instrument (Keyence KS-1000) equipped with an electric stage. The removed test piece was placed horizontally with the convex surface facing up, scanned at intervals of 1mm, and the bulge in the central part was regarded as warpage for measurement. The absolute value of the difference in the warpage before and after treatment, i.e. |(warpage after treatment) - (warpage before treatment)|, was evaluated as shape stability.
[0315] [Example 1]
[0316] <Laminate>
[0317] A synthetic resin laminate was formed using a multilayer extruder having a single screw extruder with a shaft diameter of 35 mm, a single screw extruder with a shaft diameter of 65 mm, a feed block connected to all the extruders, and a T-die connected to the feed block. Optimas 7500 manufactured by Mitsubishi Gas Chemical Co., Ltd. was continuously introduced into the single screw extruder with a shaft diameter of 35 mm as a high hardness resin (B1), and extruded under the conditions of a barrel temperature of 240°C and a discharge rate of 2.6 kg / h. In addition, a polycarbonate resin (manufactured by Mitsubishi Engineering-Plastics Corporation, trade name: IUPILON S-1000) was continuously introduced into a single screw extruder with a shaft diameter of 65 mm, and extruded under the conditions of a barrel temperature of 280°C and a discharge rate of 50.0 kg / h. The feed block connected to all the extruders was equipped with two double-layer distributors, the temperature of which was set to 270°C, and the high hardness resin (B1) and the polycarbonate resin were introduced for lamination. The sheet was extruded into a sheet form by a T-die connected to the front end at a temperature of 270°C, and cooled while transferring the mirror surface by three mirror-finished rollers set at temperatures of 120°C, 130°C, and 190°C from the upstream side, to obtain a laminate of a high-hardness resin (B1) layer (high-hardness resin layer) and a polycarbonate resin layer (base material layer). The thickness of the obtained laminate was 1.0 mm, and the thickness of the high-hardness resin (B1) layer was 60 μm near the center.
[0318] Among them, Optimas 7500 manufactured by Mitsubishi Gas Chemical Co., Ltd. used as the high hardness resin (B1) is a copolymer resin comprising a (meth)acrylate structural unit (a) represented by the above general formula (1) and an aliphatic vinyl structural unit (b) represented by the above general formula (2). In this case, the total ratio of the above (meth)acrylate structural unit (a) and the above aliphatic vinyl structural unit (b) is 99 mol% of the total structural units of the above copolymer resin, and the ratio of the above (meth)acrylate structural unit (a) is 75 mol% of the total structural units of the above copolymer resin.
[0319] <Photocurable resin composition (Y-1)>
[0320] A mixture of 60 mass % of U6HA (hexafunctional urethane acrylate oligomer, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.), 35 mass % of #260 (1,9-nonanediol diacrylate, manufactured by Osaka Organic Chemical Industry Co., Ltd.) and 5 mass % of a fluorine-based leveling agent was taken as 100 mass parts, and 3 mass parts of photoinitiator I-184 (manufactured by BASF (compound name: 1-hydroxy-cyclohexyl phenyl ketone)) was added to obtain a photocurable resin composition (Y-1).
[0321] <Patterned PET film (Z-1)>
[0322] 22.7 parts by mass of an acrylic ultraviolet curable resin (solid content 100%, trade name: Light Acrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 0.3 parts by mass of silica fine particles (NP-30, average particle size 4 μm, manufactured by AGC Si-Tech Co., Ltd.) were mixed with 77 parts by mass of MEK, and 3 parts by mass of a photoinitiator (trade name Omnirad184, manufactured by IGM Resins) were mixed by an external addition method and stirred to prepare a coating liquid (i). Next, the coating liquid (i) was applied to a PET (polyethylene terephthalate) film so that the dry film thickness was 2.5 μm, dried at 80° C. for 2 minutes, and then cured by irradiating ultraviolet rays at a line speed of 1.5 m / min using a conveyor equipped with a high-pressure mercury lamp with a light source distance of 12 cm and a power of 80 W / cm, to prepare a patterned PET film (Z-1).
[0323] The photocurable resin composition (Y-1) was applied on the high hardness resin (B1) layer of the laminate of the high hardness resin (B1) layer (high hardness resin layer) and the polycarbonate resin layer (base material layer) by a bar coater so that the thickness of the cured coating film was 5 to 10 μm, and the patterned PET film (Z-1) was covered and crimped in such a way that the pattern was in contact with the coating liquid. Then, the film was cured by irradiating with a metal halide lamp (20 mW / cm) at a light source distance of 12 cm for 30 seconds, and then the patterned PET film was peeled off to obtain an anti-glare laminate having a hard coating layer with concavoconvexities on the high hardness resin layer (B1).
[0324] [Example 2]
[0325] An anti-glare laminate was produced in the same manner as in Example 1 except that the following high hardness resin (B3) was used instead of the high hardness resin (B1).
[0326] The high hardness resin (B3) is prepared as follows. That is, 75% by mass of RESISFY R100 (manufactured by Denki Kagaku Kogyo Co., Ltd.) as a styrene-unsaturated dicarboxylic acid copolymer (E) and 25% by mass of methyl methacrylate resin Parapet HR-L (manufactured by Kuraray) as a resin (D) containing a vinyl monomer are added and mixed with a stirrer for 30 minutes. Next, an extruder with a screw diameter of 26 mm (manufactured by Toshiba Machine, TEM-26SS, L / D≈40) is used to melt-knead at a barrel temperature of 230°C, extrude into strands, and then pelletize with a pelletizer to obtain a high hardness resin (B3). The pelletization is stable.
[0327] [Example 3]
[0328] An anti-glare laminate was produced in the same manner as in Example 1 except that the following high hardness resin (B6) was used instead of the high hardness resin (B1).
[0329] The high hardness resin (B6) is prepared as follows. That is, 50% by mass of XIBOND 160 (manufactured by Polyscope) as a styrene-unsaturated dicarboxylic acid copolymer (C) and 50% by mass of methyl methacrylate resin Parapet HR-L (manufactured by Kuraray) as a resin containing a vinyl monomer (D) are added and mixed with a stirrer for 30 minutes. Next, an extruder with a screw diameter of 26 mm (manufactured by Toshiba Machine, TEM-26SS, L / D≈40) is used to melt-knead at a barrel temperature of 230°C, extrude into strands, and then pelletize with a pelletizer to obtain a high hardness resin (B6). The pelletization is stable.
[0330] [Example 4]
[0331] An anti-glare laminate was produced in the same manner as in Example 1 except that the following patterned PET film (Z-2) was used instead of the patterned PET film (Z-1).
[0332] <Patterned PET film (Z-2)>
[0333] The following coating solution (ii) was used instead of the coating solution (i) to prepare a patterned PET film (Z-2).
[0334] The coating liquid (ii) is prepared by mixing 22.6 parts by mass of an acrylic ultraviolet curable resin (solid content 100%, trade name: Light Acrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 0.4 parts by mass of silica particles (NP-30, average particle size 4 μm, manufactured by AGC Si-Tech Co., Ltd.) in 77 parts by mass of MEK, and adding 3 parts by mass of a photoinitiator (trade name Omnirad 184, manufactured by IGM Resins Co., Ltd.) and stirring.
[0335] [Example 5]
[0336] An anti-glare laminate was produced in the same manner as in Example 1 except that the following patterned PET film (Z-3) was used instead of the patterned PET film (Z-1).
[0337] <Patterned PET film (Z-3)>
[0338] The following coating solution (iii) was used instead of the coating solution (i) to prepare a patterned PET film (Z-3).
[0339] The coating liquid (iii) is prepared by mixing 22.8 parts by mass of an acrylic ultraviolet curable resin (solid content 100%, trade name: Light Acrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 0.2 parts by mass of silica particles (NP-30, average particle size 4 μm, manufactured by AGC Si-Tech Co., Ltd.) in 77 parts by mass of MEK, and adding 3 parts by mass of a photoinitiator (trade name Omnirad 184, manufactured by IGM Resins Co., Ltd.) and stirring.
[0340] [Example 6]
[0341] An anti-glare laminate was produced in the same manner as in Example 1 except that the following patterned PET film (Z-4) was used instead of the patterned PET film (Z-1).
[0342] <Patterned PET film (Z-4)>
[0343] The following coating solution (iv) was used instead of the coating solution (i) to prepare a patterned PET film (Z-4).
[0344] The coating liquid (iv) is prepared by mixing 27.7 parts by mass of an acrylic ultraviolet curable resin (solid content 100%, trade name: Light Acrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 0.8 parts by mass of silica particles (NP-30, average particle size 4 μm, manufactured by AGC Si-Tech Co., Ltd.) in 71.5 parts by mass of MEK, and adding 3 parts by mass of a photoinitiator (trade name Omnirad 184, manufactured by IGM Resins Co., Ltd.) and stirring.
[0345] [Example 7]
[0346] An anti-glare laminate was produced in the same manner as in Example 1 except that the following patterned PET film (Z-5) was used instead of the patterned PET film (Z-1).
[0347] <Patterned PET film (Z-5)>
[0348] The following coating solution (v) was used instead of the coating solution (i) to prepare a patterned PET film (Z-5).
[0349] The coating liquid (v) is prepared by mixing 19.4 parts by mass of an acrylic ultraviolet curable resin (solid content 100%, trade name: Light Acrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 0.6 parts by mass of silica particles (NP-30, average particle size 4 μm, manufactured by AGC Si-Tech Co., Ltd.) in 80 parts by mass of MEK, and adding 3 parts by mass of a photoinitiator (trade name Omnirad 184, manufactured by IGM Resins Co., Ltd.) and stirring.
[0350] [Example 8]
[0351] An anti-glare laminate was produced in the same manner as in Example 1 except that the following patterned PET film (Z-6) was used instead of the patterned PET film (Z-1).
[0352] <Patterned PET film (Z-6)>
[0353] The following coating solution (vi) was used instead of the coating solution (i) to prepare a patterned PET film (Z-6) having a dry film thickness of 4.0 μm.
[0354] The coating liquid (vi) is prepared by mixing 19.4 parts by mass of an acrylic ultraviolet curable resin (solid content 100%, trade name: Light Acrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 0.6 parts by mass of silica particles (NP-30, average particle size 4 μm, manufactured by AGC Si-Tech Co., Ltd.) in 80 parts by mass of MEK, and adding 3 parts by mass of a photoinitiator (trade name Omnirad 184, manufactured by IGM Resins Co., Ltd.) and stirring.
[0355] [Example 9]
[0356] An anti-glare laminate was produced in the same manner as in Example 1 except that methyl methacrylate resin Parapet HR-L (manufactured by Kuraray, weight average molecular weight 90,000, pencil hardness 2H) was used instead of the high hardness resin (B1).
[0357] [Comparative Example 1]
[0358] An anti-glare laminate was produced in the same manner as in Example 1 except that the following patterned PET film (Z-7) was used instead of the patterned PET film (Z-1).
[0359] <Patterned PET film (Z-7)>
[0360] The following coating solution (vii) was used instead of the coating solution (i) to prepare a patterned PET film (Z-7).
[0361] The coating liquid (vii) is prepared by mixing 27.0 parts by mass of an acrylic ultraviolet curable resin (solid content 100%, trade name: Light Acrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 1.5 parts by mass of silica particles (NP-30, average particle size 4 μm, manufactured by AGC Si-Tech Co., Ltd.) in 71.5 parts by mass of MEK, and adding 3 parts by mass of a photoinitiator (trade name: Omnirad 184, manufactured by IGM Resins Co., Ltd.) and stirring.
[0362] [Comparative Example 2]
[0363] An anti-glare laminate was produced in the same manner as in Example 1 except that the following patterned PET film (Z-8) was used instead of the patterned PET film (Z-1).
[0364] <Patterned PET film (Z-8)>
[0365] The following coating solution (viii) was used instead of the coating solution (i) to prepare a patterned PET film (Z-8).
[0366] The coating liquid (viii) is prepared by mixing 9.5 parts by mass of an acrylic ultraviolet curable resin (solid content 100%, trade name: Light Acrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 0.5 parts by mass of silica particles (NP-30, average particle size 4 μm, manufactured by AGC Si-Tech Co., Ltd.) into 90.0 parts by mass of MEK, and adding 3 parts by mass of a photoinitiator (trade name: Omnirad 184, manufactured by IGM Resins Co., Ltd.) and stirring.
[0367] [Comparative Example 3]
[0368] An anti-glare laminate was produced in the same manner as in Example 1, except that the patterned PET film was replaced with C-50G-100 (Z-9) manufactured by Nakajima Industries, Ltd., instead of the patterned PET film (Z-1).
[0369] [Comparative Example 4]
[0370] An anti-glare laminate was produced in the same manner as in Example 1 except that a hard coat layer was formed as described below.
[0371] That is, 50 parts by mass of an acrylic ultraviolet curable resin (solid content 100%, trade name: Light Acrylate DPE-6A, manufactured by Kyoeisha Chemical Co., Ltd.), 0.3 parts by mass of silica particles (octylsilane-treated fumed silica, average primary particle size 1.9 μm, trade name: SE6050-SYB, manufactured by Admatechs Co., Ltd.) were mixed into 50 parts by mass of MEK, and 3 parts by mass of a photoinitiator (trade name: IRGACURE 184, manufactured by Toyota Chemiplas Corporation) was added and stirred to prepare a photocurable composition (Y-2).
[0372] The photocurable composition (Y-2) was applied onto the high hardness resin layer using a bar coater to a coating thickness of 2.5 μm after curing, and dried at 80° C. for 2 minutes. The coating was cured by irradiation with a metal halide lamp (20 mW / cm) at a light source distance of 12 cm for 30 seconds while nitrogen was purged to obtain an anti-glare laminate.
[0373] The anti-glare laminates obtained in Examples 1 to 9 and Comparative Examples 1 to 4 are shown in Table 1 below.
[0374] [Table 1]
[0375]
[0376] In Examples 1 to 9 and Comparative Examples 1 to 4, the interface expansion area ratio (Sdr), arithmetic mean height (Sa), autocorrelation length (Sal), haze, imaging properties, glare, SW hardness, and shape stability were evaluated. The results are shown in Table 2 below.
[0377] [Table 2]
[0378]
[0379] The results in Table 2 also show that Examples 1 to 9 have excellent anti-glare properties because Sdr, Sa and Sal satisfy equations (i) to (iii). It is also confirmed that Examples 1 to 8 using high-hardness resins (B1), (B3) or (B6) also have excellent shape stability.
[0380] On the other hand, since Sdr and Sa did not satisfy the formulas (i) and (ii) in Comparative Examples 1 and 2, the anti-glare property was insufficient. In addition, the anti-glare property was also insufficient from the viewpoint of haze and imaging properties.
[0381] In Comparative Example 3, since Sa and Sal did not satisfy the formulas (ii) and (iii), the anti-glare property was insufficient. In addition, the anti-glare property was also insufficient from the perspective of imaging properties and glare.
[0382] In addition, since Sdr of Comparative Example 4 does not satisfy formula (i), the anti-glare property is insufficient. In addition, from the perspective of glare, it is also confirmed that the anti-glare property is insufficient. Since the hard coating layer contains silica particles, the glare increases and the SW hardness is insufficient.
Claims
1. An anti-glare laminate, characterized in that: At least a substrate layer containing a polycarbonate resin a1, a high hardness resin layer containing a high hardness resin B, and a hard coating layer are sequentially arranged, and the interface expansion area ratio Sdr, arithmetic mean height Sa, and autocorrelation length Sal of the hard coating layer satisfy the following formulas (i) to (iii): 0≤Sdr≤0.6 (i) 0≤Sa≤0.16 (ii) 0≤Sal≤15.0(iii).
2. The anti-glare laminate according to claim 1, wherein The interface extension area ratio Sdr, arithmetic mean height Sa and autocorrelation length Sal of the hard coating layer satisfy the following formulas (iv) to (vi): 0≤Sdr≤0.3 (iv) 0.03≤Sa≤0.13 (v) 3.0≤Sal≤8.0(vi).
3. The anti-glare laminate according to claim 1 or 2, characterized in that: The anti-glare laminate has a warpage change of 350 μm or less after being kept in an environment of a temperature of 85° C. and a relative humidity of 85% for 120 hours.
4. The anti-glare laminate according to any one of claims 1 to 3, wherein The high-hardness resin layer has a thickness of 10 to 250 μm.
5. The anti-glare laminate according to any one of claims 1 to 4, wherein The total thickness of the base material layer and the high-hardness resin layer is 100 to 3000 μm.
6. The anti-glare laminate according to any one of claims 1 to 5, wherein The hard coating layer does not contain organic particles and inorganic particles.
7. The anti-glare laminate according to any one of claims 1 to 6, wherein The polycarbonate resin a1 contains a component derived from a monohydric phenol represented by the following general formula (5): In the formula, R 5 represents an alkyl group having 8 to 36 carbon atoms or an alkenyl group having 8 to 36 carbon atoms, R 6 Each independently represents a hydrogen atom, a halogen, or an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms which may have a substituent, and n is an integer of 0 to 4, wherein the substituent is a halogen, an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 12 carbon atoms.
8. A vehicle-mounted display device, characterized in that: The anti-glare laminate comprises the anti-glare laminate according to any one of claims 1 to 7.
9. A touch panel front protection plate, characterized in that: The anti-glare laminate comprises the anti-glare laminate according to any one of claims 1 to 7.
10. A front panel for office automation equipment, portable electronic equipment or television, characterized in that: The anti-glare laminate comprises the anti-glare laminate according to any one of claims 1 to 7.
11. A method for producing an anti-glare laminate, for producing the anti-glare laminate according to any one of claims 1 to 7, wherein the method comprises: The method comprises the steps of pressing a polyethylene terephthalate film with a pattern onto the surface of a hard coating layer and transferring the concavo-convex shape so that the hard coating layer after the transfer satisfies the following formulas (i) to (iii), 0≤Sdr≤0.6 (i) 0≤Sa≤0.16 (ii) 0≤Sal≤15.0(iii).
Citation Information
Patent Citations
Antiglare laminate
JP2010160398A
Transparent product and method for producing transparent product
CN110622047A
Optical laminate, method for manufacturing same, and use thereof
CN114585951A
Anti-glare laminate
CN114929479A